Radar-aided communication scheduling algorithm for 5G and beyond networks - Jaradat, Ahmad Mohammad; Naeem, Ahmed; Sağlam, Mehmet İzzet; Kartal, Mesut; Arslan, Hüseyin (IEEE-Institute of Electrical and Electronics Engineers Inc., 2022)
Radar and communication coexistence is an upcoming technology with numerous research opportunities in the medium access control (MAC) layer, particularly in scheduling and radio resource management (RRM). More efficient scheduling algorithms are needed with the wide range of applications that the wireless environment is experiencing. We investigate an echo-based scenario in the radar-aided vehicular communication system in which an echo is reflected from a target. Unlike the conventional scheduling mechanisms where signal-to-interference-plus-noise ratio (SINR) is exploited, this paper proposes a new radar-aided communication scheduling algorithm by utilizing parameters such as range and velocity with the classical SINR measurements. The proposed algorithm schedules the available resources by extracting information from the radar echo. The proposed radar-aided communication scheduling scheme provides a more flexible design by adding new parameters, resulting in a more efficient algorithm in a broad variety of scenarios. The proposed scheme is beneficial for B5G communication systems that allow localization and sensing as key features of next-generation wireless networks.
Keywords: Radar-Aided Communication Scheduling; Range; Medium Access Control (MAC); Radio Resource Management (RRM); Scheduling; Signal-to-Interference-Plus-Noise Ratio (SINR); Velocity; 5G New Radio (NR); Beyond (B5G)